Fattening heifers on milo grain and sorghum silage. - Baker, F.H.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Milo grain and sorghum silage are extensively used in fattening rations for beef cattle in Kansas. A fattening ration composed of milo grain and sorghum silage contains sufficient protein to meet the recommended protein allowances of fattening beef cattle. It seems possible that the protein supplement fed with such a ration could be materially reduced it not completely eliminated.
Keywords: Beef; Milo grain; Sorghum silage; Protein